Understanding the molecular basis of insect pest resistance in Triticum aestivum using mass spectrometry - Lavergne, Florent D., author; Heuberger, Adam, advisor; Broeckling, Corey, committee member; Pearce, Stephen, committee member; Jahn, Courtney, committee member (Colorado State University. Libraries, 2018)
Bread wheat (Triticum aestivum L.) is a global staple crop and controlling for environmental stress that impacts grain yield is critical. Recently, Wheat Stem Sawfly (Cephus cinctus, hereafter WSS) has emerged as a new pest of wheat and is expanding across the Great Plains and southern United States. WSS is difficult to control using chemical, cultural or biological pest management methods. Currently, wheat breeders utilize a solid-stem trait to inhibit larval feeding and reduce lodging, however this trait only confers partial resistance and is thought to reduce grain yield. Models of metabolic-based resistance with demonstrated impact on reduction of insect pest fitness have been documented. Here, I investigate the broader hypothesis that wheat resistance to WSS is mediated by shifts in metabolism that promote avoidance and toxicity towards WSS. Four cultivars with contrasting phenotypes are used in our studies: Hatcher (resistant to WSS, hollow-stem, winter wheat); Conan (resistant, semi-solid-stem, spring); Denali (susceptible, hollow-stem, winter); and Reeder (susceptible, hollow-stem, spring). The first part of this work involved gas chromatography-mass spectrometry (GC-MS) metabolomics methods to provide a comprehensive characterization of the chemical composition of wheat cuticular waxes. A total of 263 putative compounds were detected among the four abovementioned wheat cultivars and comprised 58 wax compounds including alkanes and fatty acids. Many of the detected wax metabolites have known associations to important biological functions such as insect pest and drought resistance. Uni- and multivariate statistics were used to evaluate metabolite distribution between tissue types (leaf, stem) and cultivars. Leaves contained more primary alcohols than stems such as 6-methylheptacosan-1-ol and octacosan-1-ol. The metabolite data were complemented using scanning electron microscopy of epicuticular wax crystals which detected wax tubules and platelets. Conan (resistant to WSS) was the only cultivar to display alcohol-associated platelet-shaped crystals on its abaxial leaf surface. The second part of this study aimed at evaluating a selection of wheat cultivars in a WSS-infested field. Cultivars with increased yield and reduced WSS infestation values were found. The molecular basis of this resistance was evaluated in a greenhouse study that characterized proteomic and metabolomic signatures of wheat stems associated with WSS infestation. Stem proteins (1832) and metabolites (1823) were detected in the same four wheat cultivars using liquid chromatography-mass spectrometry. During infestation with WSS, 62 proteins and 29 metabolites were differentially regulated in the hollow-stem resistant cultivar Hatcher. Metabolic processes that were associated with resistance included enzymatic detoxification, proteinase inhibition, and anti-herbivory compound production, specifically the benzoxazinoids, neolignans, and phenolics. Compared to the semi-solid and resistant cultivar Conan, hollow-stem Hatcher had increased abundance of proteins and metabolites with known roles in plant defense against insects. These results will be invaluable to plant breeders as they contribute to the understanding of wax composition and metabolic regulation associated with important phenotypic traits in a major crop, including passive and active defense mechanisms to WSS.
Zip file contains supplementary tables.